Association of increased CD8+ and persisting C-reactive protein levels with restenosis in HIV patients after coronary stenting. (1st June 2016) - Schneider, Simon; Spinner, Christoph D.; Cassese, Salvatore; Promny, Dominik; Hapfelmeier, Alexander; Byrne, Robert A.; Baumann, Marcus; Jäger, Hans; Steinlechner, Eva; Laugwitz, Karl-Ludwig; Kastrati, Adnan
Abstract : Objectives: The life expectancy of HIV-infected patients has recently been increasing. Although the mortality and morbidity associated with AIDS is decreasing, those associated with cardiovascular diseases and percutaneous coronary intervention (PCI) are receiving greater attention. Only limited data regarding coronary restenosis are available in these patients. Design: In this prospective, systematic angiographic follow-up study, we enrolled HIV patients who underwent PCI for de-novo lesions and subsequent routine angiographic follow-up for 6–8 months. Angiographic restenosis was defined as stenosis of at least 50% of the in-segment area. Methods: Univariate and multivariate analyses were performed to evaluate restenosis and its predictors. Results: Between May 2002 and March 2014, 47 patients with HIV underwent PCI in two high-volume centers in Munich, Germany. Of these patients, 41 with 131 de-novo lesions underwent invasive surveillance. One-quarter of the lesions treated subsequently presented with restenosis. Univariate analysis indicated that CD8 + T-cell levels ( P  = 0.006), serum cholesterol ( P  = 0.042) and low-density lipoprotein-cholesterol ( P  = 0.042) levels at baseline, total number of stents ( P  = 0.047), and C-reactive protein level ( P  = 0.001) at follow-up were associated with restenosis. Multivariate analysis indicated that CD8 + T-cell levels ( P  = 0.006) and persistent C-reactive protein elevation at 6-month follow-up ( P  = 0.00013) were independent predictors of restenosis. Conclusion: Inflammation, represented by CD8 + T-cell levels, and persistent C-reactive protein elevation are independent predictors of angiographic restenosis and should therefore be closely monitored in HIV patients undergoing PCI.